The influence of TQM elements towards organizational performance: A case of Universiti Utara Malaysia - Lai, Xin Ying; Radzuan, Kamaruddin (Universiti Utara Malaysia, 2020)
Total quality management (TQM) is one of the most recognized models for operational excellence. Organizations implement this TQM strategy to enhance their overall performance and to maintain a competitive advantage. TQM elements included customer focus, leadership, continuous improvement, employee involvement, and process approach. TQM practices and its influences on organizational performance of UUM has still limited especially ones in the higher education industry. The main purpose of this study is to investigate the influence of TQM elements on organizational performance. The study was conducted in Universiti Utara Malaysia (UUM). The contribution of this study attempts to provide a comprehensive understanding of how TQM elements would influence on organizational performance.